Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio Can be Useful Markers for Distinguishing Uterine Adenomyosis and Leiomyoma - Yusuf Madendag; Erdem Sahin; Emine Aydin; Ilknur Col Madendag; Gokhan Acmaz; Hatice Karaman (Medical Network, 2018)
Objectıve: Both pelvic masses and preoperative diagnosis of them have still continued as an important investigation subject. It is important to discriminate the diagnoses of leiomyoma and adenomyosis before operation especially among infertile patients. Neoplasm can alter systemic or local immune response in their originating area. We aim to investigate using new inflammation markers, neutrophil to lymphocyte ratio and platelet to lymphocyte ratio, whether they are useful to discriminate between adenomyosis and leiomyoma. Study Design: We reviewed a database of all patients that had complaint from abnormal uterine bleeding resistant to medical treatment or detected pelvic mass in perimenopausal period and underwent hysterectomy in our department between January 2011 and July 2016 for study groups. However, a total of 124 patients (44 adenomyosis and 80 leiomyoma) were evaluated because of exclusion criteria and matched with 72 women who were healthy and had normal uterus and ovaries as a control group. Results: Neutrophil and platelet count, neutrophil to lymphocyte ratio and platelet to lymphocyte ratio levels were significantly higher in adenomyosis group than in control group (p=0.039, p=0.046, p=0.001 and p=0.046 respectively). Neutrophil count and neutrophil to lymphocyte ratio levels were significantly higher in adenomyosis group than in leiomyoma group (p=0.039 and p=0.001, respectively). Conclusıon: As a result, high neutrophil count and neutrophil to lymphocyte ratio levels may be useful marker to discriminate between adenomyosis and leiomyoma. Therefore, the examinations, which are more invasive and more expensive such as magnetic resonance imaging, may be less need by the agency of combined use of those inflammation markers and ultrasound in preoperative period.